Role of direct immunofluorescence in dermatological disorders - Vijaya V Mysorekar; T K Sumathy; A L Shyam Prasad (Wolters Kluwer Medknow Publications, 2015)
Background: Direct immunofluorescence (DIF) test for tissue-bound autoantibodies, has been found to be of value in the diagnosis of several dermatological disorders. The location and pattern of deposition of immunoreactants helps in classifying various immune-mediated diseases. Aims and Objectives: The aim of this study was to analyze the concordance between the clinical, histopathological and DIF diagnosis in bullous and nonbullous lesions of the skin, and thus determine the impact of immunofluorescence on diagnosis. Materials and Methods: A total of 215 skin biopsies performed in suspected immune-mediated vesiculobullous disease, vasculitis or dermatosis, were studied. Histopathological examination was done along with DIF study for deposits of immunoglobulin G(IgG), IgA, IgM, and C3. Results: Direct immunofluorescence was positive in 103/215 cases. There was very good concordance between the clinical, histological and DIF results (observed agreement = 93.4%, κ =0.90, with 95% confidence interval = 0.86-0.94). The overall sensitivity of DIF in immune-mediated skin disorders was 98.0%. DIF was positive in 52/53 cases (98.1%) in the pemphigus group and 24/25 (96.0%) bullous pemphigoid cases. None of the clinically suspected cases of dermatitis herpetiformis showed DIF positivity. A positive lupus band test was seen in 9/9 (100%) cases of lupus erythematosus. DIF was positive in 10/10 (100%) clinically suspected cases of Henoch-Schönlein purpura. In 110 cases, negative DIF results helped to rule out immune-mediated vesiculobullous disorders, lupus erythematosus and vasculitis, and the final diagnosis was made on the basis of the clinical features and/or histopathology. Conclusion: Direct immunofluorescence is a useful supplement for the accurate diagnosis of immune-mediated dermatological disorders, and helps to classify various autoimmune bullous disorders. When the clinical features/histopathology are inconclusive, the diagnosis often can be made on the basis of the DIF findings alone. A combination of the clinical features, histopathology and DIF usually gives the best results.